The Effectiveness of a Home Exercise Program for a Young Athlete with Schmorl's Nodes: A Case Report - Christian C. Evans; Amy J. Swain (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2014)
Background and Purpose: Adolescent soccer players are often prone to low back pain and one source of low back pain incurred by adolescents is Schmorl's nodes, or end-plate disc herniations. Patients with low back pain due to Schmorl's nodes are often given home exercise programs to manage their symptoms and increase their core stability. The purpose of this case report is to describe the treatment and outcome for a young athlete with Schmorl's nodes causing low back pain and lower extremity weakness.  Case Description: A 12 year-old female soccer player with a history of low back pain was referred to physical therapy with a diagnosis of Schmorl's nodes. Following 8 weeks of physical therapy, the patient was then discharged to a home exercise program. The patient underwent a 7-week home exercise program involving core strengthening exercises designed to decrease her low back pain and help her return to playing soccer with one-hundred percent effort. Outcomes: The patient completed her 7-week home exercise program. Following intervention, the patient demonstrated improvements in lower extremity and core strength as well as improvements in athletic performance. The intervention did not result in significant changes in the patient's low back pain.  Discussion: Home exercise programs are effective in the management of low back pain in young athletes. However, the effectiveness of a home exercise program for adolescent athletes with Schmorl's nodes is not well established. The home exercise program in this case was effective in increasing the patient's strength, but not at decreasing the patient's pain. More research is needed to determine the best physical therapy treatment and optimal home exercise program for adolescents with Schmorl's nodes.